Comparative Analysis Of Stock Prices, Stock Returns, And Stock Liquidity Before And After The Stock Split In Banking Companies Listed On The Idx In 2021-2023 - Reza Saputra Sihotang; Idham Lakoni; Sintia Safrianti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research seeks to compare stock prices, abnormal returns (as a proxy for stock returns), and trading volume activity (TVA) (as a proxy for liquidity levels) before and after a stock split. Utilizing an event study approach, observations were conducted on the average stock prices, abnormal returns, and TVA for five days before and five days after the stock split. Secondary data were employed with purposive sampling techniques. The data utilized in this study comprise the stock split announcement dates, which are treated as the event date (t+0), the daily closing stock prices of companies undergoing stock splits within the observation period, the daily traded share volume, the total shares outstanding, and the daily Composite Stock Price Index (IHSG). The sample consisted of three banking companies listed on the IDX that carried out stock splits between 2021 and 2023. The results reveal no significant differences in stock prices, abnormal returns, and TVA before and after the stock split.